2020
DOI: 10.1097/md.0000000000018895
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of rhubarb combined with ulinastatin for patients with sepsis

Abstract: Background: Sepsis is the leading cause of death in critically ill patients. Ulinastatin (UTI), a protease inhibitor, and rhubarb, used as a traditional Chinese medication, are proved to be effective in treating sepsis, but the effect of the combination therapy of these two drugs on sepsis remains unclear. This study aimed to investigate the effect of the combination treatment of UTI and rhubarb on sepsis patients. Methods: A total of 75 septic patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Although there is no difference on mortality results together with our study, our study did not report the effect of ulinastatin on the length of ICU stay. Ulinastatin combined with other inflammatory modifiers (such as thymosin α1) has proved that enhancing cell-mediated immunity can restore immune function, which is expected to reduce mortality [17] .…”
Section: Resultsmentioning
confidence: 99%
“…Although there is no difference on mortality results together with our study, our study did not report the effect of ulinastatin on the length of ICU stay. Ulinastatin combined with other inflammatory modifiers (such as thymosin α1) has proved that enhancing cell-mediated immunity can restore immune function, which is expected to reduce mortality [17] .…”
Section: Resultsmentioning
confidence: 99%
“…[ 25 ] During the past few years, ulinastatin is reported to treat patients with SS. [ 26 32 ] Although previous studies reported ulinastatin in treating patients with SS, [ 26 32 ] most of them involved other similar medication, and very few studies addressed the efficacy and safety of ulnastatin for the treatment of SS. In addition, there are still inconsistent results among those studies.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there are still inconsistent results among those studies. [ 26 32 ] Thus, there is still insufficient evidence to support ulnastatin for the treatment of patients with SS. This retrospective study aimed to appraise the efficacy and safety of ulnastatin for SS.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, both UTI and TM have been found to have therapeutic effects on sepsis (Jiang et al 2018;Wu et al 2019;Wang et al 2019;Ashina et al 2020), and more meaningfully, a number of studies have shown that UTI combined with other drugs can effectively improve the treatment effect of sepsis (Meng et al 2020;Wang et al 2020). At present, there are many research projects on sepsis, but the research based on drug combination therapy is not su cient.…”
Section: Introductionmentioning
confidence: 97%